Global Citizenship in Foreign Language Education Concepts, Practices, Connections - Lütge, Christiane; Merse, Thorsten; Rauschert, Petra (Routledge Studies in Language and Intercultural Communication, 2023)
In light of increasing globalization, this collection makes the case for global citizenship education as a way forward for transforming foreign language learning and teaching to better address current and future global challenges in times of unprecedented change.　 The volume maps a multi-dimensional approach within foreign language pedagogy to take up the challenge of ""educating the global citizen"". Drawing on sociocultural, pedagogical, cosmopolitan, digital, and civic-minded perspectives, the book explores the challenges in constructing epistemological frameworks in increasingly global environments, the need for developing context-sensitive educational practices, the potential of linking up with work from related disciplines, and the impact of these considerations on different educational settings. The collection reflects an international range of voices, attuned to global and local nuances, to offer a holistic compilation of conceptual innovations to showcase the relevance of global citizenship issues in foreign language education and encourage future research. This book will be of interest to scholars in intercultural education, foreign language education, and language teaching, as well as policymakers and foreign language teachers.